AKTIVITAS ANTIOKSIDAN KOMPONEN FUNGSIONAL TEPUNG DAUN KELOR (Moringa oleifera Lam) The Effect of Drying Temperature and Time on Antioxidant Activity and Functional Component of Drumstick Powder (Moringa Oleifera Lam)) (UPN VETERAN JAWA TIMUR, 2017)
AbstractDrumstick (Moringa oleifera Lam.) the most widely cultivated species of amonogeneric family Moringaceae that grows in the tropics. Drumstick leaveshave about 7 - 12 m, compound leaves, and small rounded. Drumstick leavescontain vitamin C (220 mg), 6.78 mg β-carotene. Leaves of Drumstick plant canbe consumed as a vegetable and used as plant medicine. The aim of thisresearch was to determine the effect of drying temperature and time on thequality of leaf powder of drumstick. The Method of this research was factorialarranged in a completely randomized design (CRD) with 2 factors and 3replications. The first factor is the drying temperature (50oC, 60oC, 70oC) and thesecond factor is the drying time (4 h, 5 h, 6 h) with the parameters measuredwere moisture content, yield, vitamin C, β-carotene, antioxidant activity,chlorophyll, phenol in drumstick leaf powder. The results showed that the besttreatment is drying at 60 oC and 5 h that produce the highest antioxidant activityof 35.777(%DPPH) with moisture content of 14.315%, 30.033% yield, levels ofVit. C 19.364 mg / g, the content of β-carotene 43.318 mg / g, f 6630.12 ppmphenol content, chlorophyll content of 0.664 mg / g.Keyword : Kelor, drumstick, antioxidant, temperature, time, leaf powderAbstrakKelor (Moringa oleifera Lam.) merupakan famili Moringaceae yangtumbuh di daerah tropis, tanaman kelor memiliki tinggi sekitar 7 shingga 12 m,daunnya majemuk, dan membundar kecil-kecil. Daun kelor memiliki kandunganvitamin C (220 mg), β-karoten 6,78 mg sebagai komponen fungsional sehinggatanaman kelor ini dapat dikonsumsi sebagai sayuran dan dijadikan tanamanobat.Tujuan penelitian adalah untuk mengetahui pengaruh suhu dan waktupengeringan terhadap aktivitas antioksidan dan komponen fungsional tepungdaun kelor. Metode penelitian ini disusun secara faktorial dalam rancangan acaklengkap (RAL) dengan 2 faktor dan 3 ulangan. Faktor pertama adalah suhupengeringan ( 50oC, 60oC, 70oC) dan faktor kedua adalah waktu pengeringan (4jam, 5 jam, 6 jam) dengan parameter yang diamati adalah kadar air, rendemen,vitamin C, β-karoten, aktivitas antioksidan, klorofil, fenol pada tepung daun kelor.Hasil penelitian menunjukan bahwa perlakuan terbaik pengeringan adalah padasuhu 60 0C dan waktu 5 jam dengan menghasilkan aktivitas antioksidan tertinggi35,777(%DPPH) dengan kandungan kadar air 14,315%, rendemen 30,033 %,kadar Vit. C 19,364 mg/g, kandungan β-karoten 43,318 μg/g, kandungan fenol6.630,12f ppm, kandungan klorofil 0,664 mg/g.Kata kunci : Kelor, antioksidan, suhu, waktu, tepung.